REVOLUTIONIZING SLEEP QUALITY: THE ROLE OF BABY MASSAGE IN TREATING PNEUMONIA PATIENTS AT PADMANABA BARAT ROOM, RSUP DR. SARDJITO - Afrilia, Duwi; Margaretha, Sumarti Endah Purnamaningsih Maria; Urrahman, Dhiya; Sulistyowati, Endang Tri (Jurnal Keperawatan PPNI Jawa Barat, 2024)
Introduction : Pneumonia is an acute respiratory tract infection that affects the lung tissue (alveoli). Sleep is a form of adaptation of babies to their environment. Baby massage is a rubbing movement on the baby's body starting from the feet, stomach, chest, face, hands and back of the baby. Based of the register book in Padmanaba Barat room, the incidence of pneumonia in the last 3 months was 22 cases. Purpose: To find out how to improve sleep quality with infant massage in pneumonia patients in the West Padmanaba ward, RSUP Dr SARDJITO Hospital, Yogyakarta. Method: The method used in this research is descriptive in the form of a case study. Results: From the implementation that was carried out for 2 days on one respondent by measuring sleep quality in the first pre-intervention with a score of 5, the first post-intervention with a score of 4 and the second pre-intervention with a score of 4, the second post-intervention with a score of 2. Conclusion: Baby massage can improve sleep quality in pneumonia patients.